Generation of Low Phase-Noise Frequency-Sextupled Signals Based on Multimode Optoelectronic Oscillator and Cascaded Mach–Zehnder Modulators - Yichao Teng; Yiwang Chen; Baofu Zhang; Jianhua Li; Lin Lu; Yong Zhu; Pin Zhang (IEEE Photonics Journal, 2016)
We have demonstrated a scheme to realize the generation of frequency-sextupled signals with low phase noise (PN). The structure is based on a multimode optoelectronic oscillator (OEO) and two cascaded Mach–Zehnder modulators (MZMs). A drive source signal is modulated by the MZM1, which is biased at the minimum transmission point (MITP); the generated first-order sidebands are injected into the multimode OEO, which is contributed by the MZM2, the single-mode fiber, the photodetector, and the amplifier. The third-order sidebands are generated by the MZM2, which is also biased at the MITP. The modulated signal is then divided into reflection components and transmission components by a fiber Bragg grating (FBG). The reflection components, including the first-order sidebands, are sent to the photodetector and fed back to the MZM2 to form an optoelectronic hybrid loop. The transmission components, including the third-order sidebands, are heterodyned by another photodetector to generate a frequency-sextupled signal. Compared with the drive signal, the generated signal has a lower PN due to the selection of the oscillation mode. In the experiment, a frequency-sextupled signal from 15 to 24 GHz is generated by a drive signal, which is tuned from 2.5 to 4 GHz. The PN of the generated signal at 24 GHz is −103.6 dBc/Hz@10 kHz; 14.6 dB PN reduction is realized.